The Effect of Kasgot Fertilizer Application on the Chemical Properties of Soil Planted with Cucumbers (Cucumis sativus L.) - Ridho Septyan; Hilwa Walida; Fitra Syawal Harahap; Ika Ayu Putri Septyani (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Sustainable agriculture requires the prudent management of natural resources, including the judicious use of fertilizers and other inputs. One of the primary challenges faced by farmers is the decline in soil fertility resulting from the prolonged use of chemical fertilizers. This study aims to evaluate the effect of Kasgot fertilizer on soil chemical properties, specifically soil pH, organic carbon content, total nitrogen (N), available phosphorus (P), and available potassium (K), in cucumber cultivation. Soil sampling was conducted using a proportional sampling method, where sample points were selected based on soil availability and were representative of the cucumber cultivation area. The results indicated that, based on the analysis of phosphorus (P) and potassium (K) nutrient content, the treatment with 5 grams per planting hole was most effective in increasing phosphorus availability to 0.2907%, classified as high. Meanwhile, the treatments with 10 grams and 20 grams per planting hole were more effective in increasing soil potassium content to 0.0724% and 0.0708%, respectively, both of which were classified as moderate to high.